Phramahākasat kap ngān sitthi manutsayachon - Kānčhanā Nāksakun (Samnakngān Khana Kammakān Sitthi Manutsayachon hǣng Chāt, 2012)
King Bhumibol Adulyadej of Thailand and his activities and work in the human rights field.